2045. Pitfalls in the Use of MALDI TOF Mass Spectrometry for the Identification of Problematic Yeast Isolates from a Historical Collection. (26th November 2018) - Pachar, Monica; Chavez, Violeta; Rodriguez, Jose; Rex, John; Pappas, Peter; Wanger, Audrey; Ostrosky-Zeichner, Luis
Abstract: Background: The identification of yeast traditionally entails macroscopic/microscopic findings and biochemical testing. Recently, MALDI TOF MS has replaced traditional methods for identification as a proposed new standard. We performed identification of previously unidentifiable yeasts from a collection in the United States. Methods: The Mycoses Study Group (MSG) collected 2, 947 Candida isolates from 1, 911 patients as part of two U.S. studies between 1995 and 1999. The identification of the isolates was done in 2002 using API 20 c aux with supplemented standard mycological and biochemical test (corn meal agar, germ tube and the Murex ID system). Ninety-four isolates could not be identified at that time. For this study, the isolates were defrosted, plated on Sabureau Dextrose agar, and incubated at 30°C for 48 hours. We then sub-cultured again in Blood Agar. Isolates when then tested by MALDI TOF MS following the methodology for the Bruker MALDI biotyper. Results: In the first attempt, 65/94 (69%) isolates were identified. The remaining 29 samples were re-tested with a yield of 21/29 (72.4%) identified isolates. The remaining isolates had to be identified with another round of MALDI TOF and further biochemical testing. The table below shows the final identification of the isolates. Conclusion: MALDI TOF MS is rapidly becoming a reference method for yeast identification. However, in a historical collection of yeast that could not be identified by conventional biochemical methods, it took up to three rounds of MALDI TOF MS with a yield of ~70% per round, and additional biochemical testing, for identification of all isolates. Continuing validation of MALDI TOF MS for identification of difficult yeast isolates is warranted. Disclosures: All authors: No reported disclosures.